Terobosan Baru Dalam Budidaya Ayam Ras Pedaging: Maksimalkan Performa Optimal Dengan Ransum Campuran Tepung Buah Mahkota Dewa - Sadarman, Sadarman; Lisman, Jon; Harahap, Anwar Efendi; Novianti, Sri; Andriani, Mira (Jurnal Peternakan Mahaputra, 2023)
The crown fruit is rich in antioxidants and anti-inflammatories, especially flavonoids, which are believed to improve broiler performance, including growth and reducing mortality. This study aims to determine the optimal concentration of crown fruit meal addition in feed on broiler performance. The research design used was a completely randomized design with crown fruit meal as the focus. Four treatments were applied, each with 5 replicates, P1: Standard feed from PT. Charoen Phokpan Indonesia Tbk., for P2, P3, and P4 added crown fruit flour as 1%, 2%, and 3% as feed, respectively. Furthermore, sixty one-day-old chicks (CP 707 strain, without sex difference) were allocated into 20 research units measuring 180 cm x 100 cm x 60 cm, with 3 chicks per unit. The observed variables were feed consumption and weight gain recorded daily from day 8 to day 35, feed conversion, and mortality rate. Data collected were analyzed using SPSS version 27.0, and differences between treatments were tested using DMRT at the 5% significance level. Results showed that there were no significant differences (P>0.05) in feed consumption, weight gain, feed conversion, and mortality. However, the mortality rate of broilers could be reduced to 0.20%. The conclusion of this study is that the addition of crown fruit flour can reduce the mortality rate of broilers due to the antioxidant and anti-inflammatory roles of crown fruit.